On the Quest for a Coherent and Unitary Theory for the Interdisciplinary Field of Communication Studies: Array - Munteanu, Cristinel; Grosu, Emanuel (Acta Universitatis Danubius. Communicatio, 2021)
The field of communication studies is an extremely various one, this diversity being generated by each and every science which deals in a specific manner with the object of communication or language in itself. However, there are great efforts nowadays to build or to identify a coherent and unitary theory or even a paradigm in order to guide, in a transdisciplinary way, the sciences of such a vast domain. One of the relevant proposals in this regard, coming from Ioan S. Cârâc, is that of considering semiotics as a transdisciplinary method or of taking as a paradigm Eugenio Coseriu’s integral linguistics.